Analisis Pengaruh Parameter Geomekanika Batuan Terhadap Kegiatan Peledakan Pada Front Penambangan Blok A2 di CV. Triarga Nusatama, Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota, Sumatera Barat - Riki Rinaldo; Bambang Heriyadi; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2018)
Determination of the geometry of the blasting and powder factor should pay attention to characteristics of rock mass and local geological conditions. Alternative geometry experiments done to apply the problem of the resulting explosion. The alternative draft geometry is determined by using the characteristics of rock mass Blastability based on Lilly's Index, in the form of rockmass description, joint plane spacing, joint plane orientation, specific gravity influence, and hardness. Based on the results of weighting the mass of rock Blastability Index values obtained are blown up as big as 54.125. From these values, the geometry of the explosion which is good for a 3 inch bore hole is a burden 3 m, spacing 2 m, a depth of 5.5 m, subdrilling 0.5 m, high level of 3.5 m, steaming of 2 m, and explosive hole long 2 m. And also the value of the powder factor 0.24 kg/m³. From the geometry of the proposal generated the desired percentage of the company's boulder and the use of explosives is lower compared to the previous applied geometry. Keywords: Charateristic of rock mass, Blastability index, Geometry, Blasting, Fragmentation